A Method to Analyze PSS from the Viewpoints of Function, Service Activity, and Product Behavior - Hara, T.; Arai, T.; Shimomura, Y. (Cranfield University Press, 2009)
As our economy matures, combination of tangible products and intangible services becomes a key issue toward a harmonious balance with economic growth and environment conscious. This paper aims to present a method for analyzing structures of service processes described in the modeling method the authors have proposed. It includes three indices of service delivery process according to customer satisfaction elements: (1) visibility to receiver, (2) interactivity with receiver, and (3) degree of receiver participation. Through an application case study, it is found that the method can indicates the features of services, and contributes to acquirement of clues for improving services.
Organised by: Cranfield University
Keywords: Product/Service-System; Service delivery process; Service blueprint; Service modeling